Conceptual Metaphor about Corona Virus: Cognitive Semantic Analysis - Irzam Sarif S; Yuyu Yohana Risagarniwa; Nani Sunarni (Makassar State University, 2021)
Abstract. Conceptual metaphors are the result of mental construction, conceptualization of the experience of human life. In Japanese, metaphorical features are often found in conveying information so that information can be easily understood. This study aimed to describe the conceptual metaphors found at the Japanese Prime Minister's Press Conference, Shinzo Abe on March 14 and 28, 2020 through the official website kantei.go.jp. The research method used was descriptive qualitative analysis. Data were collected by taking text that contained metaphorical elements and then selected. Data selection was based on the basic principle of metaphor, which was the mapping from the source domain to the target domain. Then the data were classified based on the type of metaphor by Lakoff and Johnson and the type of image scheme by Cruse and Croft. Based on the study done, there were three types of conceptual metaphors, 1) Structural metaphors with conceptuals meaning of enemy, medical treatment, control, and mind; 2) Orientational metaphors with conceptual meaning of disadvantage, and approval; 3) Ontological metaphors with conceptuals meaning of finance, and emotion. In addition, there were also six types of image schemes, namely the image scheme of Strength, Existence, Identity, Scale, Space, and Unity.Keywords: Conceptual Meaning, Press Conference, Cognitive Semantic, Image Scheme